THE INFLUENCE OF TAXATION KNOWLEDGE AND TAX AWARENESS ON UMKM TO TAXPAYER COMPLIANCE IN THE SPECIAL PROVINCE OF YOGYAKARTA - Negara, Hari Kusuma Satria; Purnamasari, Dian Indri (Faculty of Business, Widya Mandala Catholic University Surabaya, Indonesia, 2018)
The aim of this research to examine whether there is an influence of Taxation Knowledge and Tax Awareness on UMKM to Taxpayer Compliance in the Special Province of Yogyakarta. By using the mail survey method, in the period of the study, respondents who returned and were ready to be analyzed were 163 respondents, namely entrepreneurs or UMKM taxpayers in Yogyakarta. All respondents according to the criteria required in this study and ready to be analyzed, namely having NPWP, UMKM turnover, final income tax payment of 1%, and domiciled in Yogyakarta. The results showed that there was no effect of tax knowledge variables on tax compliance, but there was an effect of tax awareness variables on tax compliance.